Key rules of life and the fading cryosphere: Impacts in alpine lakes and streams. (19th October 2020) - Elser, James J.; Wu, Chenxi; González, Angélica L.; Shain, Daniel H.; Smith, Heidi J.; Sommaruga, Ruben; Williamson, Craig E.; Brahney, Janice; Hotaling, Scott; Vanderwall, Joseph; Yu, Jinlei; Aizen, Vladimir; et al.
Abstract: Alpine regions are changing rapidly due to loss of snow and ice in response to ongoing climate change. While studies have documented ecological responses in alpine lakes and streams to these changes, our ability to predict such outcomes is limited. We propose that the application of fundamental rules of life can help develop necessary predictive frameworks. We focus on four key rules of life and their interactions: the temperature dependence of biotic processes from enzymes to evolution; the wavelength dependence of the effects of solar radiation on biological and ecological processes; the ramifications of the non‐arbitrary elemental stoichiometry of life; and maximization of limiting resource use efficiency across scales. As the cryosphere melts and thaws, alpine lakes and streams will experience major changes in temperature regimes, absolute and relative inputs of solar radiation in ultraviolet and photosynthetically active radiation, and relative supplies of resources (e.g., carbon, nitrogen, and phosphorus), leading to nonlinear and interactive effects on particular biota, as well as on community and ecosystem properties. We propose that applying these key rules of life to cryosphere‐influenced ecosystems will reduce uncertainties about the impacts of global change and help develop an integrated global view of rapidly changing alpine environments. However, doing so will require intensive interdisciplinary collaboration and international cooperation. More broadly, the alpine cryosphere is an example of a system where improving our understanding of mechanistic underpinnings of living systems might transform our ability to predict and mitigate the impacts of ongoing global change across the daunting scope of diversity in Earth's biota and environments. Abstract : Several fundamental physical and chemical properties of living things constitute potential "rules of life" that can help improve predictions about how organisms and ecosystems will respond to changing conditions, such as climate change. These rules include the temperature dependence of biological processes, the fundamental impacts of ultraviolet light, the core elemental requirements of living things, and how resource use efficiency structures ecosystems. This paper describes how these four rules can help in predicting how alpine lakes and streams will respond to future changes in the influence of glaciers and snowpack as climate change unfolds.